Amino acid digestibility of different rye genotypes in caecectomised laying hens. Issue 6 (1st November 2016) - Zuber, Tobias; Miedaner, Thomas; Rosenfelder, Pia; Rodehutscord, Markus
ABSTRACT: This study investigated the variability of amino acid (AA) digestibility of rye grains in laying hens. Relationships between AA digestibility and physical properties (thousand seed weight, test weight, falling number, and extract viscoelasticity), chemical composition (proximate nutrients, non-starch polysaccharides, AA, minerals, and inositol phosphates), gross energy concentration, and in vitro solubility of nitrogen (N) of the grains were also examined. Twenty rye genotypes were grown under standardised agronomic and environmental conditions as part of a collaborative research project known as "GrainUp". Each genotype was added to a basal diet at 500 g/kg at the expense of maize starch to produce 20 rye diets. The experimental design comprised four Latin Squares (6 × 6) distributed over two runs, resulting in 12 experimental periods. Caecectomised laying hens (LSL-Classic) were individually kept in metabolism cages. Excreta were collected quantitatively for 4 d, and AA digestibility of the rye genotypes was determined using a regression approach. The digestibility of AA was generally low but varied significantly among the 20 rye genotypes, especially for Lys (digestibility range 35–59%), Met (57–75%), Thr (34–54%), and Trp (36–71%). Nevertheless, physical and chemical characteristics as well as the in vitro solubility of N correlated in only a few cases with AA digestibility. Multiple linear regression was used to calculate equations to predict AA digestibility based on the analysed characteristics. However, their explanatory power, as judged by the adjusted R 2, was not sufficiently precise for practical application (below 0.6 for most AA). In conclusion, the AA digestibility of rye grain is generally low and varies significantly between crop genotypes. Equations based on its physical and chemical characteristics are not sufficiently precise to be useful for feed formulation.